Waste water heat recovery system - Markovič, G.; Vranayová, Z.; Káposztasová, D. (Видавництво Львівської політехніки, 2016)
After heating and cooling, water heating is typically the second largest user of energy in the home. There are a lot of purposes and uses of hot water in buildings - showers, tubs, sinks, dishwashers and clothes washers etc. In most cases, these hot waste waters are discarded direct to sewer system. When we take into the account all of these purposes in every households, the wastewater retains a considerable portion of its initial energy – energy that could be recovered and used. The cold water that is put into a water heating device can be preheated using the reclaimed thermal energy from a appliance such a shower so that the input water doesn't need as much energy to be heated before being used in a shower, dishwasher, or sink. The water entering a hot water tank is usually close to 12 °C but by recovering the energy in the hot water from a bath or dishwasher, the temperature of the water entering the holding tank can be elevated to 23–25 °C. Installing a waste water heat recovery systems reduces energy consumption and thus greenhouse gas emissions and the overall energy dependency of the household. There are two basic ways how to capture heat from wastewater produced by all sources in a building and to put it to use - require a regenerator-type double-walled heat exchanger or a non-regenerative, straightforward heat exchanger can be used. Heat exchanger systems of each type are available for use in buildings. This paper contains brief overview of the waste water heat recovery system as a way of reducing of overall energy consumption in building as well as sustainable way of capturing and recovering heat within the building. Після систем опалення та охолодження, системи гарячого водопостачання є другим за величиною споживачем енергії в домашніх умовах. Є багато потреб і використання гарячої води в будинках: душові кабіни, ванни, раковини, посудомийні і пральні машини тощо. У більшості випадків гарячі стічні води скидаються безпосередньо в систему каналізації. Якщо врахувати всіх споживачів в домашньому господарстві, стічні води зберігають значну частину своєї первісної енергії – енергії, яку можна залучити і використати. Холодну воду, яка міститься в водогрійному пристрої, можна попередньо нагріти за допомогою утилізованої теплової енергії, наприклад, водою після душу. Температура води, яка надходить в бак для гарячої води, як правило, близько 12 °C, а при використанні енергії від гарячої води з ванної або посудомийної машини температуру води, що надходить в збірний резервуар, можна збільшити до 23–25 °С. Установка систем рекуперації тепла стічних вод знижує споживання енергії і, отже, викиди парникових газів та загальну енергетичну залежність домашнього господарства. Є два основні способи отримання тепла від стічних вод з усіх джерел в будівлі: використання регенератора з подвійними стінками або нерегенеративний – з використанням простого теплообмінника. Теплообмінники системи кожного типу доступні для використання в будівлях. У цьому документі міститься короткий огляд системи утилізації тепла стічних вод як спосіб зниження загального споживання енергії в будівлі, а також сталий спосіб уловлювання та рекуперації тепла в будівлі.
Keywords: exchanger; ventilation heat losses; recovery; waste water; теплообмінник; тепло; відновлення; стічні води